ARTERIAL HYPERTENSISON IN POSTMENOPAUSAL WOMEN: CURRENT POSSIBILITIES OF MEDICAL THERAPY IN OUT-PATIENTS - B. J. Bart; G. M. Boronenkov; V. F. Benevskaya (Российский кардиологический журнал, 2001)
Arterial hypertensison in postmenopausal women: current possibilities of medical therapy in out-patients.